Altas habilidades ou superdotação :indicação, intervenção e práticas colaborativas - Wenzel, Chaiane (Universidade Federal de São Carlos, 2025)
Gifted students, who are part of Special Education, have guaranteed rights to specialized educational support and, to this end, they must be identified and receive it, providing them with opportunities for their differentiated abilities. One possibility for school staff to work with special education students is the collaborative teaching. Based on this, the research problem is: how would an intervention program from a collaborative perspective contribute to the visibility of students with indications of giftedness in the 1st and 2nd years of elementary school in a school of the municipal education network in an inland city of São Paulo, Brazil? The main objective was to create an intervention program by a collaborative perspective for gifted students in the 1st and 2nd years of elementary school in a public school of inland of São Paulo. The specific objectives were: 1. to identify gifted students with characteristics in the 1st and 2nd years of elementary school; 2. to suggest the creation of a collaborative intervention program for gifted students; and 3. to survey and indicate points and gaps in teacher training on giftedness. The study was divided into three sections and characterized as being of the Pedagogical Intervention as a qualitative empirical research. The first section consisted of training teachers about giftedness; the second one involved nominating students using questionnaires and portfolios; and the third one involved creating a collaborative intervention program for the nominated students. The participants were: 150 students, classroom teachers, a PE teacher, the principal, vice-principal and coordinator. The results were: a) the school staff did not have consistent knowledge about giftedness to identify students; b) 26 students were nominated; c) a collaborative intervention program was created with the teachers and the 26 nominated students (second section); d) three activities were planned: Mathematics, Astronomy, and Science according to the interests of seven students (third section); e) It was observed the difficulty of time to implement the Collaborative Intervention Program even though it was proved to be effective; e) the specialized literature showed a scarcity of work focused on giftedness and collaborative teaching. It is suggested continuing the intervention program for these students as well as evaluating to be improved and implemented for all the students nominated and the other ones at the school.
High abilities or giftedness: indication, intervention and collaborative pratices
Keywords: Educação Especial; Altas habilidades ou superdotação; Ensino Colaborativo; Co-ensino; Special Education; Giftedness; Collaborative teaching; Co-teaching; CIENCIAS HUMANAS::EDUCACAO